2012
DOI: 10.1590/s0074-02762012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Distinct cytokine profiles of circulating mononuclear cells stimulated with Staphylococcus aureus enterotoxin A in vitro during early and late episodes of chronic osteomyelitis

Abstract: We investigated the cytokine profile of peripheral mononuclear cells from chronic osteomyelitis (OST) patients following in vitro stimulation with staphylococcal enterotoxin A (SEA). We demonstrate that stimulation with SEA induced prominent lymphocyte proliferation and high levels of tumour necrosis factor (TNF)-α, interleukin (IL)-4 and IL-10 secretion in both OST and non-infected individuals (NI). Even though stimulation with SEA had no impact on IL-6 production in either patient group, the baseline level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In line with previously published data showing the inductive effects of S. aureus with regard to the expression of pro-inflammatory cytokines in different cell types [ 62 , 63 ] including osteoblasts [ 28 ], we found that the most persistent and at the same time most toxic strain, ST239, was able to strongly increase the expression levels of IL-6 and TNF-α, two cytokines often over-expressed during the development and progression of osteomyelitis [ 64 , 65 , 66 , 67 ] at both 3 and 24 h p.i. compared with other strains.…”
Section: Discussionmentioning
confidence: 59%
“…In line with previously published data showing the inductive effects of S. aureus with regard to the expression of pro-inflammatory cytokines in different cell types [ 62 , 63 ] including osteoblasts [ 28 ], we found that the most persistent and at the same time most toxic strain, ST239, was able to strongly increase the expression levels of IL-6 and TNF-α, two cytokines often over-expressed during the development and progression of osteomyelitis [ 64 , 65 , 66 , 67 ] at both 3 and 24 h p.i. compared with other strains.…”
Section: Discussionmentioning
confidence: 59%
“…It is common to see that IL‐10 shows a transient decrease in the early stage of osteomyelitis and then gradually increases subsequently. [ 67 ] In the immune microenvironment of osteomyelitis, monocytic cells can upregulate Toll‐like receptor 3 (TLR3) gene expression in response to the internalized S. aureus or its extracellular vehicles (EVs), then activate the NF‐κB pathway, and promote significant secretion of IL‐10. [ 68 ] Admittedly, IL‐10 is considered an important M2 marker, which acts as an anti‐inflammatory cytokine.…”
Section: Resultsmentioning
confidence: 99%
“…Cytokine signature -the cut off points for major and minor producers of cytokines were established based on a global median computation of all participants for each cytokine. Based on this approach, the individuals of each group were classi ied as major or minor producers (14,15) Activities protocol…”
Section: Immunological Assessmentmentioning
confidence: 99%
“…The absolute values in pg/mL of the seven cytokines under study were extremely low, close to the minimum detection threshold The characterization of serum cytokines was based on the frequency of individuals classi ied as major and minor producers. That is, the values obtained by the experimental (pre-exercise and postexercise) and control groups were compiled into a single group and the median was calculated and adopted as the cut off point for each cytokine under study ( Figure 3A), based upon which the participants were classi ied as minor or major producers (14,15) .…”
Section: Quantifi Cation Of Cytokinesmentioning
confidence: 99%